Novel green management strategies for fruit flies (Tephritidae: Diptera) infesting horticultural crops in India: a critical review - Rashmi, M A; David, K J; Verghese, Abraham (Current Horticulture, 2025)
Fruit flies, in the family Tephritidae, are major pests of horticultural crops and of quarantine concern in India and globally due to their concealed feeding habits and invasive nature. In India, most problematic species belong to the genera Bactrocera, Dacus, and Zeugodacus within the subfamily Dacinae, and Carpomya within the subfamily Trypetinae. The economic impact of these pests extends beyond yield losses and increased management costs. They can also lead to the loss of export markets and increased expenses for the construction and maintenance of fruit treatment and management facilities. Approximately 40 species of Tephritidae have been intentionally or unintentionally introduced outside their natural ranges by humans. Notable examples include Bactrocera dorsalis (Hendel), B. carambolae Drew and Hancock, B. latifrons (Hendel), Zeugodacus cucurbitae (Coquillett), and B. zonata (Saunders), which have spread from the Oriental region to other parts of the world. Conversely, B. oleae (Rossi) was introduced from the Mediterranean region to India. Beyond their role as pests, some fruit flies are significant as biological control agents for invasive weeds. Over 20 species, primarily from the subfamily Tephritinae, have been used to manage invasive Asteraceae species.